THE EFFECT OF FERMENTED DRAGON FRUIT SKIN JUICE THROUGH DRINKING WATER ON CUT WEIGHT AND PERCENTAGE OF QUAIL CARCASS PARTS - M. I., Herawati; Dewi, G. A.M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
The primary objective of this study is to examine the impact of providing fermented dragon fruit peel juice through drinking water on the cut weight and carcass parts percentage of quails. The study utilized a completely randomized design (CRD) with three treatments and six replications, involving a total of 180 quails at 12 weeks of age. The treatments involved quails with drinking water that did not contain fermented dragon fruit peel juice. (P1), quails drinking water containing 4% fermented dragon fruit peel juice (P2), and quails drinking water containing 6% fermented dragon fruit peel juice (P3). The observed variables were slaughter weight, carcass 219 weight, carcass percentage, and percentage of carcass parts (breast, thigh, wing, and back) in quails. The results of the study revealed that treatments P2 and P3 showed significantly higher values than P1 (P<0.05) in terms of slaughter weight and carcass weight. However, no significant difference (P>0.05) was observed among treatments P2 and P3 compared to P1 regarding carcass percentage and percentage of carcass parts (breast, thigh, wing, and back). It can be concluded that the administration of 4% and 6% fermented dragon fruit peel juice through drinking water can increase the slaughter weight and carcass weight of quails, but it has not been able to increase the carcass percentage and percentage of carcass parts (breast, thigh, wing, and back) significantly.